Presbycusis: A Brain Disorder? “The Ears Listen, the Brain Hears” - Gates, George A. (Seminars in Hearing, 2012)
Age-related hearing loss (presbycusis) is the most common cause of hearing loss. The audiometric profile of peripheral presbycusis is well known, but little attention has been paid to the role of central auditory dysfunction in both the diagnosis and management of presbycusis. Central presbycusis is typified by difficulty understanding speech in noise. Central presbycusis appears to involve or arise from decrements in executive functioning, which may be age-related or dementia-related. Tests employing speech in noise are appropriate measures for identifying patients who understand speech relatively normally in quiet but have undue difficulty understanding in background noise. The message of this discussion is that such testing should be done routinely for patients complaining of this problem. Identification of central presbycusis with such testing is important for proper auditory rehabilitation.
Keywords: hearing loss; dementia; working memory; executive function; central auditory processing